Does sequential decision-making trigger collective investment in automobile R&D? Experimental evidence - Tobias Buchmann; Alexander Haering; Muhamed Kudic; Michael Rothgang (RWI - Leibniz-Institut für Wirtschaftsforschung, 2018)
We conduct a framed laboratory experiment to gain in-depth insights on factors that drive collective research and development efforts among firms located along the automotive value chain. In particular, we employ a public goods experiment and analyze the influence of sequential decision-making on the willingness to engage in cooperation and on economic welfare. By using a linear value chain setting with three suppliers and one OEM, we analyze vertical R&D cooperation. Our results reveal that contributions increase in situations with sequential decision-making and that sequential decisions increase the overall welfare, even in case of unequally distributed R&D budgets. – – Wir verwenden ein ökonomisches Laborexperiment um Einblicke in Faktoren zu gewinnen, welche die gemeinsame Forschungs- und Entwicklungsarbeit von Unternehmen entlang der Wertschöpfungskette in der Automobilindustrie vorantreiben. Dabei setzen wir ein 'öffentliches Gut Experiment' ein und analysieren den Einfluss sequentieller Entscheidungen auf die Kooperationsbereitschaft sowie die Wohlfahrt. Hierfür modellieren wir eine lineare Wertschöpfungskette mit drei Lieferanten und einem OEM und analysieren vertikale F&E-Kooperationen. Unsere Ergebnisse zeigen, dass die Beiträge zum gemeinsamen Forschungsprojekt bei sequentiellen Entscheidungen zunehmen und dass sequentielle Entscheidungen die Wohlfahrt erhöhen. Dies gilt auch bei ungleich verteilten F&E-Budgets.
Keywords: C92; D79; O31; 330; public goods experiment; collective innovation; automobile industry; value chain; innovation barriers; sequential decision making